Anomalous levels in the southern Portuguese continental shelf sedimentary record: potential evidence of the 1755 CE Lisbon Tsunami - Kümmerer, Vincent (2021)
At present, knowledge about tsunami event deposits in outer shelf environments with water depths > 60 m is limited, although understanding of the involved processes as tsunami induced erosion of seafloor sediments and induced backwash currents are critical for tsunami hazard assessment. Both, incoming tsunami waves and generated backwash currents can leave signatures in the offshore sedimentary record. Preservation of tsunami imprints seems more likely in offshore deposits as in onshore deposits, which are in contrary more regarded. Thus, a multidisciplinary approach was conducted to detect probable imprints left by the 1755 Lisbon tsunami event in 3 cores from the southern Portuguese continental shelf with water depths > 57 m. Age model results, based on 14C and 210Pb ages, confirm the ages of the sediment to the 1755 Lisbon tsunami event. Other extreme events such as storms can be excluded trough hydrodynamic considerations. Implementing new high-resolution methodologies as the multivariate analyses of sand composition and microtextural features on quartz grain surfaces yielded more evidence for a tsunamigenic origin of previous detected high energy event layers in the studied core sections in the context of ASTARTE project, although no remarkable terrigenous signal is present. The heterogenous and mixing character of the probable 1755 Lisbon offshore tsunami deposits coupled with hydrodynamic considerations suggest, that subunits related to different tsunami wave incursions and backwash phases re unlikely to be preserved in similar environments as the study area. Also, spatial depositional differences of tsunami sediments were encountered in the study area by differences in mean grain size, sand composition, and simulated horizontal surface velocities. The new applied methodologies contribute paleo-tsunami layer identification and facilitate new studies on offshore tsunami deposits. While the southern Portuguese shelf seems to be a very good study area, we suggest for near future works to collect multiple cores aligned in transects for a better understanding of tsunami sedimentation dynamics